Analysis of Basic Soccer Skills: A Survey Study of Extracurricular Students - Irvan Irvan; Waskito Aji Suryo Putro; Saiful Anwar; Harmaman Harmaman; Leo Pratama (Jurnal Porkes, 2026)
Background.Basic soccer technical skills are a fundamental component in the development of school-age players that determine the quality of their performance; however, the implementation of skill assessment in extracurricular activities remains suboptimal and tends to lack a data-driven approach. Objectives. This study aims to analyze the level of basic soccer technical skills among students participating in an extracurricular program, focusing on off-the-ball technical aspects and ball control as a basis for evaluating the training program. Methods. This study employs a quantitative approach with a descriptive design. The study sample consisted of 25 students selected using total sampling. Data were collected through tests and measurements using the David Lee Soccer Potential Circuit Test, which includes a 20-meter run, ball-less skills, and ball-handling skills. Data were analyzed using descriptive statistics, including mean values, standard deviations, frequency distributions, and percentages, with the assistance of SPSS software. Results. The results of the study indicate that the level of students’ basic soccer technical skills was predominantly in the “good” category at 52%, followed by the “fair” and “poor” categories at 16% each, the “very poor” category at 12%, and the “excellent” category at 4%. Ball-handling and off-the-ball skills fell into the good to very good categories, while running speed remained in the fair category. Conclusion. This study indicates that the development of basic technical skills in extracurricular activities has been fairly effective; however, improvements are needed in physical aspects, particularly speed. These findings contribute as a basis for evaluating and developing training programs that strike a better balance between technical and physical aspects to enhance the quality of soccer training in schools.